2022
DOI: 10.18528/ijgii220052
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymphatic interventional radiology for postoperative lymphorrhea

Abstract: Lymphorrhea after gastrointestinal surgery may be treated conservatively or surgically, and treatment by lymphatic interventional radiology has also recently come into use. From pedal lymphangiography, intranodal lymphangiography was widely adopted, enabling the site of lymphorrhea to be identified and its approach to be planned, and embolization for lymphorrhea is now becoming feasible in an increasing number of patients. Even for patients in whom embolization is infeasible, identifying the site of leakage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…13 However, accessing axillary, cervical, para-aortic, or mesenteric lymph nodes is feasible alternative if lymph nodes can be punctured. 3 Local anesthesia of the puncture site using 1% lidocaine is administered. The inguinal or femoral lymph node is then punctured using a 23-gauge Cathelin needle (Terumo Europe, Leuven, Belgium), which is preconnected to a short connector and a small syringe filled with lipiodol, under ultrasound guidance with a high-frequency linear probe.…”
Section: Intranodal Lymphangiographymentioning
confidence: 99%
See 4 more Smart Citations
“…13 However, accessing axillary, cervical, para-aortic, or mesenteric lymph nodes is feasible alternative if lymph nodes can be punctured. 3 Local anesthesia of the puncture site using 1% lidocaine is administered. The inguinal or femoral lymph node is then punctured using a 23-gauge Cathelin needle (Terumo Europe, Leuven, Belgium), which is preconnected to a short connector and a small syringe filled with lipiodol, under ultrasound guidance with a high-frequency linear probe.…”
Section: Intranodal Lymphangiographymentioning
confidence: 99%
“…Lipiodol injection should be intermittently observed by fluoroscopy to monitor that the needle has not slipped out of the lymph node, which may cause largevolume lipiodol leakage into the surrounding soft tissues or into the vein. 3 A previous review revealed that the technical success of these lymphangiography procedures was achieved in 95.1% (387/407) of the patients who underwent pedal (361: 88.7%) and intranodal lymphangiographies (46: 11.3%). Other patients (20: 4.9%) encountered technical failures, with unsuccessful pedal lymphatic vessel cannulation as the main cause.…”
Section: Intranodal Lymphangiographymentioning
confidence: 99%
See 3 more Smart Citations